Hubungan Status Pekerjaan, Pendidikan Formal Dan Pengetahuan Ibu Dengan Pemberian ASI Eksklusif Pada Balita Di Posyandu Lestari, Kelurahan Kumpulrejo Kec.Argomulyo, Salatiga - Bakti, Imam; , Dwi Sarbini, S.ST., M.Kes; , Luluk Ria Rakhma, S.Gz., M.Gizi (2016)
Introduction: One of the expected goals in the development which is being carried out is the increase in the quality of human resources (HR) as the basis for the establishment of quality human capital, starting from babies in the womb along with mother's milk breastfeeding from the early age, especially exclusive mother's milk breastfeeding. There are several factors influencing the exclusive breastfeeding include maternal employment , formal education and knowledge. The percentage of exclusive mother's milk breastfeeding at Posyandu (Integrated Service Post) Lestari, Village of Kumpulrejo, Sub-District of Argomulyo, Salatiga is still low (35.6%), under the Minimum Service Standard targets for achievement of exclusive mother's milk breastfeeding in Salatiga Town by 80 %. Purpose: The purpose of the study is determining the relationship between the employment status, formal education as well as the knowledge of mothers and the exclusive mother's milk breastfeeding in Posyandu Lestari, Village of Kumpulrejo, Sub-District of Argomulyo, in Salatiga. Method of Investigation: The design of investigation is cross sectional. The sample consists of mothers who have toddlers between the ages of 7 to 24 months, as many as 35 respondents. Data about mother's employment status, mother's formal education, mother's knowledge about exclusive mother's milk and exclusive mother's milk breastfeeding were obtained from questionnaire interviews. Data were analyzed using Chi-Square test. Results: A total of 62.9% of respondents did not work, 65.9% of respondents were highly educated, 54.3% of respondents were with unfavorable knowledge and 54.3% of respondents did not give exclusive mother's milk. Conclusion: There was a relationship between employment status of mothers and the level of mothers' knowledge with exclusive mother's milk breastfeeding. There was no relationship between mothers' education and exclusive mother's milk breastfeeding. Suggestions : Increase the knowledge of mothers on the importance of exclusive breastfeeding , by extension through meetings dasa wisma , gathering PKK . Keywords : Exclusive mother's milk, children, employment, education, knowledge Bibliography : 31: 2000-2014